Phase I study of tomuzotuximab, a glycoengineered therapeutic antibody against the epidermal growth factor receptor, in patients with advanced carcinomas - Fiedler, Walter; Cresta, Sara; Schulze-Bergkamen, Henning; Dosso, Sara De; Weidmann, Jens; Tessari, Anna; Baumeister, Hans; Danielczyk, Antje; Dietrich, Bruno; Goletz, Steffen; Zurlo, Alfredo; Salzberg, Marc; et al. (ESMO open, 2018)
<Background: Changes in glycosylation of the constant domain (Fc) of monoclonal antibodies (mAbs) enhance antibody-dependent cell-mediated cytotoxicity independently of downstream effects following receptor blockade by the antibody, thus extending their indication. We investigated the safety, pharmacokinetics, pharmacodynamics and antitumour activity of tomuzotuximab, an IgG1 glycoengineered mAb against the epidermal growth factor receptor with enhanced tumour cytotoxicity in a phase I dose-escalation study (NTC01222637). Patients and methods: Forty-one patients with advanced solid tumours refractory to standard therapies received tomuzotuximab weekly (12-1370 mg) or two-weekly (990 mg) on a three-plus-three dose escalation design. Results: A maximum tolerated dose was not reached. The most frequent treatment-related adverse events were infusion-related reactions in 31 (76%) patients (grade 3, 12%), mainly confined to the first dose, and skin toxicities (grade 1 or 2) in 30 (73%) patients. Hypomagnesaemia was observed in 9 out of 23 evaluable patients (39%). Similar to cetuximab, tomuzotuximab concentrations increased proportionally to dose from doses≥480 mg with a median terminal half life (t½) of 82 hours, range 55-113 hours. Antitumour activity included one complete response ongoing since more than 4.5 years in a patient with non-small-cell lung cancer and one partial response lasting 353 days in a patient with colorectal cancer. Twelve patients achieved stable disease (median, 166 days, range, 71-414 days) and two patients had prolonged control (>1 year) of their non-measurable disease. Conclusion:: Tomuzotuximab was safe and showed promising antitumour activity in heavily pretreated patients with advanced metastatic disease. A phase IIb trial of chemotherapy and weekly tomuzotuximab or cetuximab followed with maintenance therapy with the corresponding mAb in patients with recurrent or metastatic head and neck squamous cell carcinoma is ongoing.
Gesehen am 17.04.2020